Cerai Gugat pada Perempuan Mandailing: Analisis Strukturasi dengan Pendekatan Mixed Methods - Muhammad Achsan Shabily; Jendrius Jendrius; Maihasni Maihasni (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Although cerai gugat (female-initiated divorce) is theoretically expected to be uncommon within the patrilineal-patriarchal Mandailing social system, judicial records consistently show that its incidence exceeded cerai talak (male-initiated divorce) in Mandailing Natal Regency from 2019 to 2023. This study examines why Mandailing women increasingly initiate divorce by analyzing their demographic characteristics, the structural factors operating at the family, customary, and state levels, and the ways in which women exercise agency within these structures. The research employed an explanatory sequential mixed methods design, integrating descriptive statistical analysis of secondary court data with qualitative data obtained through in-depth interviews, participant observation, and document analysis. The findings demonstrate that women's families of origin (mora) function as essential sources of allocative resources and authoritative resources, while customary institutions, including halang batang and pasahatkon, together with formal legal institutions, provide legitimate mechanisms through which women negotiate and pursue divorce. The study concludes that Mandailing women are not merely constrained by patriarchal structures but actively mobilize enabling structural resources to exercise agency and make autonomous marital decisions, thereby illustrating the dynamic interplay between structure and agency as conceptualized in Anthony Giddens' structuration theory.